2016
DOI: 10.1111/ddi.12436
|View full text |Cite
|
Sign up to set email alerts
|

Seed release in a changing climate: initiation of movement increases spread of an invasive species under simulated climate warming

Abstract: Aim Reliable estimates of how species will move under future climatic conditions are lacking, and the ability of species to track suitable habitat under climate change is strongly predicated on dispersal. In wind‐dispersed plants, initiation of movement by maternal seed release characteristics can affect the ultimate shape of the dispersal kernel. If seed dispersal traits respond to altered local abiotic conditions induced by climate change during development, the effects could have major impacts on projection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 60 publications
2
24
0
4
Order By: Relevance
“…Common to most theoretical and empirical studies is the basic assumption portraying invasive spread as a spatially continuous process, characterized by the (very) low probabilities of extreme LDD (or jump dispersal) events at the dispersal kernel tail . This basic assumption prevails in both classic (Skellam 1951;Okubo et al 1989;Allen et al 1991) and contemporary literature (Adams et al 2015;Uden et al 2015;Teller, Zhang & Shea 2016). However, the findings of the current study suggest that Fig.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Common to most theoretical and empirical studies is the basic assumption portraying invasive spread as a spatially continuous process, characterized by the (very) low probabilities of extreme LDD (or jump dispersal) events at the dispersal kernel tail . This basic assumption prevails in both classic (Skellam 1951;Okubo et al 1989;Allen et al 1991) and contemporary literature (Adams et al 2015;Uden et al 2015;Teller, Zhang & Shea 2016). However, the findings of the current study suggest that Fig.…”
Section: Discussionsupporting
confidence: 46%
“…; Uden et al . ; Teller, Zhang & Shea ). However, the findings of the current study suggest that the occurrence of such long jumps cannot be consistently estimated based on a continuous fat‐tailed dispersal kernel.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Jongejans et al () and Soons and Bullock () found morphological mechanisms that facilitate short‐term synchronisation of seed release with optimal wind conditions showing low air humidity and high wind speeds (respectively). Such synchronisations of seed release timing and optimal conditions for long‐distance dispersal are increasingly considered important for the assessment of species’ ability to reach suitable habitats (Teller et al ). Our result of the existence of enhanced conditions for long‐distance seed dispersal by wind during seed release can be cautiously interpreted as a phenological adaptation i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating dispersal kernels may involve measuring seed shadows (Clark 1998), identifying and quantifying multiple dispersal vectors (Nathan et al 2008), measuring average lifetime displacement or converting from a measured distribution of dispersal distances to a dispersal kernel (Cousens & Rawlinson 2001). Recent advanced approaches to parameterizing IDE dispersal kernels include using climate projections to fit wind dispersal models (Bullock et al 2012), collecting onsite data on wind speed and tree canopy heights (Caplat, Nathan & Buckley 2012), incorporating complex movement of dispersal vectors such as birds (Neupane & Powell 2015), and using experimental warming to anticipate changes in seed release rates (Teller, Zhang & Shea 2016). For MHMs, it is common to select a flexible family of dispersal kernels or to rely on the type of kernel commonly used for a particular taxon.…”
Section: Laying Foundations: a Basic Mhmmentioning
confidence: 99%